High-frequency microwave diagnostics of of free and bound water content in biological objects - Бондаренко, И.Н.; Гордиенко, Ю.Е.; Нечипоренко, А.С.; Панченко, А.Ю. (Radiotekhnika, 2019)
Most biomaterial molecules are electrically neutral. Electrophysical properties of a biomaterial molecule are acquired when water molecules having a pronounced dipole moment bind to them. Therefore, the solution to the problem of determining the relationship of water with biological macromolecules and creation of methods for monitoring the state of water in biological objects is a step in the general problem of diagnosing their state. The composition of biological macromolecules, proteins includes intramolecular water. This affects both the real and the imaginary part of the dielectric constant of biological objects. The study is based on the fact that water has the greatest effect on the dielectric constant of the media in which it is located. With complex molecules of a biological substance, water can have bonds various in nature. Therefore, there is a significant set of physical factors associated with obtaining information about the state of biological objects based on determining the amount and distribution of free and integrated water in macromolecules of biological substances using microwave sensors relative to biological objects in vivo and in vitro, as well as during external exposure to them. The main ideas are based on the fundamental principles of radio physical methods for obtaining values of the real and imaginary parts of the dielectric constant in the frequency range of relaxation of macro-molecules of biological media with bound and free water. Information on the content and changes in the distribution of free and bound water in biological objects makes it possible to diagnose their state. Microwave diagnostics of biological objects using resonator transducers with coaxial probe structures provide an opportunity for non-destructive analysis with millimeter and submillimeter spatial resolution. Analytical methods were used to study the nature of the interaction of electromagnetic fields created by coaxial apertures of various configurations with samples. Based on the results obtained, the directions for the implementation of microwave high-local diagnostics techniques are determined.